Open-labeled, multicenter phase II study of prophylactic administration of pegylated granulocyte colony-stimulating factor in relapsed or refractory multiple myeloma who received pomalidomide-based regimens (KMM170) - Song, Ga-Young; Lee, Je-Jung; Moon, Joon Ho; Kim, Dajung; Kim, Min Kyoung; Kim, Hyo Jung; Mun, Yeung-Chul; Lee, Won-Sik; Do, Young Rok; Lee, Jae Hoon; Jung, Sung-Hoon; Kim, Jin Seok (Frontiers in Oncology, 2023)
Pegylated granulocyte colony-stimulating factor (G-CSF) has been widely used for preventing febrile neutropenia in various types of cancer treatment. In the present study, we prospectively evaluated the safety and efficacy of pegfilgrastim as a primary prophylaxis of febrile neutropenia and infection among patients with relapsed refractory multiple myeloma (RRMM) treated with pomalidomide-based regimens. Thirty-three patients with RRMM who received pomalidomide and dexamethasone (Pd) with or without cyclophosphamide (PCd) were enrolled in this study. Twenty-eight patients were treated with PCd and 5 patients were treated with Pd. All patients were given pegfilgrastim subcutaneously with a single administration performed on the first day of each cycle as primary prophylaxis until the fourth cycle. The median age of the patients was 75 (range 56-85), and the median prior line of therapy was 2 (range 2-6). Seventeen patients (51.5%) had any grade of neutropenia and 20 (60.6%) had any grade of thrombocytopenia before starting pomalidomide treatment. During the 4 cycles of treatment, grade 3 or more neutropenia occurred in 17 patients (51.5%), and 4 (12.1%) experienced grade 3 or more febrile neutropenia. Grade 3 or more infections occurred in 5 patients (15.2%). Interestingly, the patients with markedly increased ANC of more than 2 x 10 9 /L compared to baseline ANC after 7 days of pegfilgrastim at 1st cycle of treatment showed a significantly lower incidence of grade 3-4 neutropenia. The most common adverse event of pegfilgrastim was fatigue, and all the adverse events caused by pegfilgrastim were grade 1 or 2. And there was no significant change in the immune cell population and cytokines during the administration of pegfilgrastim. Considering that this study included elderly patients with baseline neutropenia, pegylated G-CSF could be helpful to prevent severe neutropenia, febrile neutropenia, or infection in patients with RRMM.